2013
DOI: 10.4067/s0717-95022013000100034
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Antioxidants in Cerebellar Development: A Review of Literature

Abstract: SUMMARY: Developmental pathologies may result from endogenous or xenobiotic-enhanced formation of reacting oxygen species (ROS), which oxidatively damage cellular macromolecules and/or alter signal transduction, and that the embryonic processes regulating the balance of ROS formation, oxidative DNA damage and repair, and ROS-mediated signal transduction may be important determinants of teratological risk. ROS can oxidize molecular targets such as DNA, protein, lipid in a process called oxidative stress resulti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 61 publications
1
11
0
Order By: Relevance
“…It neutralizes free radicals, stimulates antioxidative enzymes, and effectively decreases oxidative stress in the central nervous system (Zhang et al, 2017). Tamura et al and Imosemi (Imosemi, 2013; Tamura et al, 2012) demonstrated the antioxidative effects of melatonin, which were in agreement with the current findings.…”
Section: Discussionsupporting
confidence: 93%
“…It neutralizes free radicals, stimulates antioxidative enzymes, and effectively decreases oxidative stress in the central nervous system (Zhang et al, 2017). Tamura et al and Imosemi (Imosemi, 2013; Tamura et al, 2012) demonstrated the antioxidative effects of melatonin, which were in agreement with the current findings.…”
Section: Discussionsupporting
confidence: 93%
“…There is a wide range of natural products with antioxidant activity that counteract oxidative stress through different mechanisms, including ROS scavenging, chelation of transition metal ions, and regulation of the expression and activity of antioxidant defense enzymes [9][10][11][12]. Several plants contain phytochemicals that could be potential suitable protective agents, such as Ginkgo biloba, Panax ginseng, Curcuma longa, Vitis vinifera, Salvia officinalis, Coffea arabica and Camellia sinensis [13].…”
Section: Introductionmentioning
confidence: 99%
“…Different classes of natural products have been identified as potential antioxidant candidates with therapeutical application in diseases linked to oxidative stress [9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…This observation could be explained by the mechanism of action of nicotine or its antioxidant effects as previously reported by Imosemi, et al in 2013. [77] Receptors in the granular layer includes glutamate receptors, nicotinic and muscarinic receptors; nicotine has been proven to enhance excitatory glutaminergic inputs by activating presynaptic α7nAchRs. [42,78] The present study did not provide a molecular basis for this observation and may be considered in future investigations.…”
Section: Discussionmentioning
confidence: 99%